Workers as Human Beings: Recognising the imago Dei in the Neoliberal Workplace - Megoran, Nick (Black theology, 2023)
This interdisciplinary article reflects theologically on what it means to be treated ethically under regimes of Human Resource Management (HRM) in the neoliberal workplace. In replacing older models of personnel management, HRM has achieved a position of dominance that raises important pastoral and ethical questions about recognition of the personhood of workers. This article contends that because critical work on HRM within the social sciences has failed to fully engage with these fundamental questions, a turn to Black theological anthropology is invaluable in understanding the ethico-political implications of HRM. Arguing that lived experiences of “the worker” are commonly missing from theological reflection on work, it advocates the interdisciplinary use of empirical research methods from the social sciences to populate the theology of work with real workers.